2020
DOI: 10.1017/s000842392000030x
|View full text |Cite
|
Sign up to set email alerts
|

Logarithmic versus Linear Visualizations of COVID-19 Cases Do Not Affect Citizens’ Support for Confinement

Abstract: The SARS-CoV-2 virus was first identified in Wuhan, China, in late December 2019, and it quickly spread to many countries. By March 2020, the virus had triggered a global pandemic (World Health Organization, 2020). In response to this crisis, governments have implemented unprecedented public health measures. The success of these policies will largely depend on the public's willingness to comply with new rules. A key factor in citizens’ willingness to comply is their understanding of the data that motivate gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 4 publications
0
29
0
Order By: Relevance
“…Finally, it is worth noting that Canada-wide support for workplace closure policies is almost uniformly high despite Canadians expecting the economy to stay closed until early August (Sevi et al, 2020). 6 This is quite an impressive achievement, for both the government and the public.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is worth noting that Canada-wide support for workplace closure policies is almost uniformly high despite Canadians expecting the economy to stay closed until early August (Sevi et al, 2020). 6 This is quite an impressive achievement, for both the government and the public.…”
Section: Resultsmentioning
confidence: 99%
“…4 Each subgroup prediction is an average across 10,000 draws from the posterior predictive distribution. 5 See footnote 5 in Sevi et al (2020). 6 The rate of support is so uniformly high that it is not worth modeling.…”
Section: Notesmentioning
confidence: 99%
“…Canadians viewed measures like mask-wearing as a means to protect others, not just themselves (van der Linden and Savoie 2020). Canadians also appeared to have formed these policy preferences based on the perceived seriousness of the pandemic and trust in the ability of government to lead appropriately (Sevi et al 2020;Mohammed, Johnston, and van der Linden, 2020). As a result, policymaking has been more cooperative in the Canadian experience.…”
Section: Discussionmentioning
confidence: 99%
“…4 The Canadian case is particularly interesting given the remarkable resilience of the population in dealing with the pandemic. Previous research has shown that Canadians were overwhelmingly supportive of social distanciation measures during the lockdown (Sevi et al, 2020;Merkley et al, 2020;Pickup, Stecula, and van der Linden, 2020), despite the presence of a rather extensive set of restrictive policies in urban areas (Armstrong and Lucas, 2020). However, we still have limited information on the public's perceptions of containment measures such as cell phone contact tracing.…”
Section: Introductionmentioning
confidence: 91%